2015
DOI: 10.1108/ijmf-02-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the cost of capital on the financing decisions of Brazilian companies

Abstract: Purpose – The purpose of this paper is to examine the market timing behavior of listed Brazilian companies to verify the effects of the cost of capital on their financing decisions, and hence on their capital structure. Design/methodology/approach – The relation between the cost of capital (debt and equity capital) and the leverage of firms in the period from 2000 to 2011 is analyzed by means of regression models with panel data. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 39 publications
3
23
0
15
Order By: Relevance
“…The signs obtained for the variables GDP growth, per capita income and inflation rate are in agreement with the signs found by et al (2009), indicating a positive relation with leverage. Regarding the participation of publicly traded companies in GDP, it is possible to infer that publicly traded companies have greater financing capacity and are seeking to finance via credit market rather than capital markets, which is common in Brazil, because most of the companies that opened capital in recent years did not return to issue primary shares, according to Albanez and Lima (2014). This positive relationship between public companies' participation in GDP and leverage is also found by Santos (2013).…”
Section: Analysis Of Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The signs obtained for the variables GDP growth, per capita income and inflation rate are in agreement with the signs found by et al (2009), indicating a positive relation with leverage. Regarding the participation of publicly traded companies in GDP, it is possible to infer that publicly traded companies have greater financing capacity and are seeking to finance via credit market rather than capital markets, which is common in Brazil, because most of the companies that opened capital in recent years did not return to issue primary shares, according to Albanez and Lima (2014). This positive relationship between public companies' participation in GDP and leverage is also found by Santos (2013).…”
Section: Analysis Of Resultsmentioning
confidence: 80%
“…The evidence found is significant and point out that the market-tobook index has a significant impact on corporate indebtedness and, consequently, in the definition of its capital structure. In Brazil, studies such as Mendes et al (2009), Rossi Jr. and Marotta (2010), Vallandro et al (2010), Albanez and Lima (2014) and Albanez (2015) found evidence in favor of the Market timing theory.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…Usually, tangible assets serve as collateral for debts (contracts covenants), the more tangible assets, the lower the creditor's risk and the larger the debt tends to be (Rajan & Zingales, 1995;Albanez, 2015). Therefore, a positive relationship between tangibility and indebtedness (leverage) is expected.…”
Section: B) Market-to-book (M/b)mentioning
confidence: 99%
“…Fatica (2018) stated that tax-adjusted user costs significantly influence capital accumulation. Albanez (2015) analysed behavior of listed Brazilian companies and concluded that in periods of more expensive equity capital, companies restructured their capital with larger share of debt. Case study by Britzelmaier et al (2013) indicated that value-based management has become a key management approach for small and medium size companies, where WACC is used to determine cost of invested capital.…”
mentioning
confidence: 99%